Pengaruh Faktor Klinik dan Pengobatan terhadap Keberhasilan Terapi Tuberkulosis pada Pasien HIV–TB di Jember (The Influences of Selected Clinical Factors and Treatment on Tuberculosis Therapy Outcome among HIV-TB Patients in Jember) - Nuraini Agustin; Afifah Machlaurin; Prihwanto Budi Subagio (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Human imunodeficiency virus (HIV) is an infectious diseases that become an international problem. Since 1980s, there was an increase in morbidity and mortality due to tuberculosis (TB) infection in high HIV prevalence areas. The success of therapy is very important in the treatment of HIV-TB patients. The purpose of this study was to determine the factors that influence the success therapy in HIV-TB patients. This research was a cross sectional study with retrospective approach and used chi square analysis. The result showed that most patients were male (62.1%) and most were 25-34 years in age (42.3%). Most HIV-TB patients were 41-50 kg in weight (56.9%). They had CD4 level range of 50-199/mm3 and total lymphocyte count (TLC) less than 1,200/mm3 (58.6%). Most HIV-TB received therapy TB category 1 that was 55.2%, and antiretroviral (ARV) combination of TDF+3TC+EFV (91.8%). Based on chi square analysis, body weight, CD4 level, and TLC affected the success therapy (P value 0.022, 0.003, 0.028), whereas age and gender didn't (P value 0.222, 0.905). On the other hand, the variation therapy of TB and HIV didn't affect the success therapy either (P value 0.943, 0.718).Keywords: HIV-TB, antiretroviral, tuberculosis therapy